2013
DOI: 10.1007/s00296-013-2699-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the use of two simultaneously TENS devices for fibromyalgia pain

Abstract: Fibromyalgia is characterized by a range of symptoms that include muscle pain, fatigue and sleep disorders. Transcutaneous electrical nerve stimulation (TENS) is an established method for pain relief. The purpose of the study was to evaluate the effectiveness and safety of the use of two simultaneously new TENS devices for fibromyalgia pain. After Ethics approval and informed consent, 39 patients were prospectively divided into three groups to evaluate TENS device, applied simultaneously in each patient: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 22 publications
1
33
1
14
Order By: Relevance
“…Our data agree with those of Moran et al [ 136 ], who stated that the sensory TENS has a significant effect in inducing hypoalgesia compared to placebo. The effects obtained in our work partly disagreed with the claims of Lauretti [ 137 ], who argues that high amplitude stimuli that cause intense muscle contraction are necessary to obtain a low frequency supraspinal effect with TENS. It is probable that the trigeminal territory stimulated with dental ULFTENS has different somatosensory central characteristics of signals integration than those found in other parts of the body, such as the dorsal lumbar and/or limbs, which can contribute to explain our results.…”
Section: Ultralow Frequency Tens (Ulftens)contrasting
confidence: 99%
“…Our data agree with those of Moran et al [ 136 ], who stated that the sensory TENS has a significant effect in inducing hypoalgesia compared to placebo. The effects obtained in our work partly disagreed with the claims of Lauretti [ 137 ], who argues that high amplitude stimuli that cause intense muscle contraction are necessary to obtain a low frequency supraspinal effect with TENS. It is probable that the trigeminal territory stimulated with dental ULFTENS has different somatosensory central characteristics of signals integration than those found in other parts of the body, such as the dorsal lumbar and/or limbs, which can contribute to explain our results.…”
Section: Ultralow Frequency Tens (Ulftens)contrasting
confidence: 99%
“…The TENS device represents an alternative for pain control and would act as an adjunctive therapy in painful menstruation. The application of active TENS induced hypoalgesia that persisted during the eight‐hour interval in the three‐ to five‐day study, and the rescue analgesics consumption was very scarce, without adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dailey et al [6] showed a one-time session of TENS (using a maximum tolerable intensity) significantly decreased movement pain and hyperalgesia. No changes were observed in resting pain [6] Lauretti et al [111] showed TENS using a strong intensity (60 mA) at two sites and at one site produced a significant decrease in pain at rest compared with placebo when applied over a seven day period. Two additional studies show reductions in pain with strong but comfortable intensity HF TENS compared with warmth therapy and to a no TENS group [110,112.] Thus, when used at a strong but comfortable sensation, TENS may be effective for both resting and movement pain in people with fibromyalgia.…”
Section: Evidence Of Tens For Pain Managementmentioning
confidence: 99%